Assessment of knowledge and attitude toward stem cells and their implications in dentistry among recent graduates of dental schools in Saudi Arabia - Adel Alhadlaq; Nassr Al-Maflehi; Saleha Alzahrani; Afnan AlAssiri (Elsevier, 2019)
Background: To evaluate the knowledge and attitude level of recent dental graduates in Saudi Arabia toward stem cells and their potential therapeutic applications. Methods: In this cross-sectional study, a questionnaire was distributed among 606 recent graduates from 14 dental schools in Saudi Arabia. Fifteen statements were formulated to address the knowledge component with "yes" or "no" or "I do not know" answer and 10 statements were designed to assess the attitude level with Likert 5-point response scale. The level of knowledge for each respondent was designated as poor if the score value is (0-5), moderate (6-10), and high (11-15). To evaluate the attitude level for each respondent, a score of (1) was assigned for extremely negative answer and (5) for extremely positive answer for each statement. Based on the total score, attitude level was considered poor when the score value is (10-29), moderately positive (30-39), good (40-44), or excellent (45-50). Results: Significant difference was found in the knowledge score between males and females (p = 0.004). Both males and females showed poor knowledge with a mean score of 5.06 ± 2.5 and 5.63 ± 2.4, respectively. There was an overall moderately positive attitude of participants toward stem cells and their therapeutic applications with a mean value of 33.15 ± 5.92 with no significant difference between males and females (p = 0.53). A significant positive linear correlation was detected between knowledge and attitude for both males (r = 0.323, p = 0.00) and females (r = 0.392, p = 0.00). Conclusion: Updating dental curricula with topics on stem cell research and potential future applications in dentistry is demanded. Keywords: Stem cells, Knowledge, Attitude, Dental education, Recent graduates, Saudi Arabia